Desmielinização e expressão de interleucina 1â, Substância P e fatores neurotróficos em modelo de dor neuropática do nervo trigêmeo - Grazielle Mara Ferreira Costa (2015)
Trigeminal neuralgia (TN) is a common neuropathic pain and is characterized by episodes of severe pain in small areas of the face. Chronic constriction injury (CCI) of the infraorbital nerve (IoN) is used as an experimental model of TN. The development of neuropathic pain occurs as a result of structural changes in injured nerve and production of inflammatory mediators and neurotrophic factors. Thus, we investigated pathological and ultrastructural alterations, demyelination and expression of neuropeptide SP, cytokine IL-1, nerve growth factor (NGF) and the glial-derived neurotrophic factor (GDNF) in trigeminal ganglion and nerve over time in CCI-IoN model in order to correlate kinetics of changes in the development of pain. Rats were submitted to CCI-IoN (IoN group) or sham surgery (SHM group). Spontaneous and evoked behavior was evaluated and recorded at 3, 6, 9, 12 and 15 days postoperatively (p.o.). At these times, tissues and serum were collected for morphological analysis by optical and electron microscopy, immunohistochemistry and protein levels of NGF and GDNF by ELISA. Initially, IoN rats showed hyporesponsiveness to mechanical stimulation and, subsequently, there was a significant increase in the response, suggesting development of mechanical allodynia. Nerve lesions with significant structural impairment, intense demyelination and glial cell proliferation was observed over time in IoN group. At day 6 days p.o., axonal damage and demyelination were more intense and at day 15 p.o., partial remyelination was observed. IL-1 immunostaining was evident in nerve fascicles and in the trigeminal ganglion of IoN animals in both weeks p.o.. Neuropeptide SP showed greater immunoreactivity only in the distal regions of IoN rats animals. There was no difference in NGF levels in serum or tissues between groups in any of the studied times. Higher seric levels of GDNF were found in SHM animals at day 6 p.o., but no difference in tissue levels of this mediator was observed in any time studied. Taken together, our results demonstrate the important role of demyelination and remyelination processes, expression of IL-1 and SP and dysfunction in GDNF production of in the development of pain over time which contributes to the understanding of mechanisms that lead to trigeminal neuropathic pain.